A framework introducing implications of RFID network threats to businesses. (2017) - Muammar, Suadad; Miniaoui, Sami
The radio frequency identification (RFID) technology is increasingly used in several industries for various business tasks (item tracking, inventory, etc.). Many types of security threats to RFID networks have been identified, but the impact of these threats on businesses remains unclear. This research aims at proposing a framework detailing the implications of RFID security threats to businesses. We followed an interpretive study to draw up the proposed framework. Based on a literature review, we established a classification of RFID usages (inventory management, payment systems, identity control, and tracking systems). A number of RFID network security threats (denial of service, spoofing, relay, etc.) were identified and explained. Consequently, a framework linking RFID threats to different types of usages in applications is proposed and explained. This framework exposes clearly the implication of every RFID threat on a specific usage of RFID regardless of the industry (healthcare, education, etc.).